Biodegradable Microplastics: A Review on the Interaction with Pollutants and Influence to Organisms - Wang, Yi; Ding, Keqiang; Ren, Lingxiao; Peng, Anping; Zhou, Shaoda (Bulletin of environmental contamination and toxicology, 2022)
Biodegradable plastics attract public attention as promising substitutes for traditional nondegradable plastics which have caused the serious white pollution problem due to their persistence. However, even for biodegradable plastics, natual conditions for the rapid and complete degradation are rare. Even more serious is that biodegradable plastics might be disintegrated into microplastics more rapidly than tranditional plastics, emerging as another threat to the environment. Similar to traditional microplastics, biodegradable microplastics could adsorb many pollutants by various physicochemical effects and release additives. Biodegradable microplastics have been confirmed to be toxic to the organisms as particle matter and the vector as pollutants. Under some conditions, biodegradable microplastics may pose more severe negative impacts on the organisms. With the fierely increasing trend to replace the nondegradable plastic commodities with biodegradable ones, it is necessary to evaluate whether biodegradable plastics and the generated microplastics would alleviate plastic pollution or induce greater ecological impacts.